EFEKTIVITAS PRENATAL YOGA TERHADAP LAMA PERSALINAN KALA II - Tauriska, Nidia Salwa; Palupi, Jenie; Umami, Riza (Malang Journal of Midwifery (MAJORY), 2022)
Childbirth complications that are directly caused by prolonged labor are 2.8% of deaths from the maternal mortality rate worldwide which is 69,000. Factors that affect the smooth delivery are power, passage, passenger, psychological and helper. One way to maximize these factors is to do prenatal yoga. Prenatal yoga can increase the elasticity of the pelvic muscles that play a role in the delivery process. The purpose of this study was to determine the effectiveness of prenatal yoga on the second stage of labor. This research is a literature review with a traditional type of review, articles taken from 3 databases (Google Scholar, PubMed, ResearchGate) from the 2017-2021 range. Screening was carried out based on the PICOT so that 10 articles were obtained (5 national and 5 international articles). All articles found that the duration of labor in the second stage of labor was shorter for mothers who did prenatal yoga than those who didn’t. Nine out of ten articles had p-value<0.05 and 1 article had p-value>0.05 which means that prenatal yoga was effective in shortening the second stage of labor. It is hoped that health workers will facilitate prenatal yoga for pregnant women because the combination of movements is useful in facilitating the delivery process